Rapid isolation of genomic DNA from Asian green-lipped mussel (Perna viridis) for random amplified microsatellite polymorphism - Chai, Lay Ching; Abdullah, Fatimah Corazon; Mat Sout, Norhisyam; Alias, Rozila; Abu Samah, Nadzirah; Lee, Natasha Hai Yen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
The objective of the present study was to develop a rapid, reliable and yet inexpensive protocol for genomic DNA extraction from frozen and ethanol-preserved Asian green-lipped mussels for random amplified microsatelite (RAM) analysis. The procedure comprised of three major steps: (1) Tissue degradation by boiling in 6% Chelex 100 resin in TE buffer; (2) Protein digestion by Proteinase K; and (3) DNA precipitation by adding 2 volumes of cold absolute ethanol. The entire procedure can be completed within two hours. The resulting RAM profiles were clear and reproducible. Our results demonstrate that the combined protocol of Chelex 100- Proteinase K-ethanol precipitation is a powerful yet economical DNA isolation method for population genetic studies involving a large sample size.